Synthesis and Characterization of New Chelating Resins Containing Thiourea as the Functional Group - Mohd Amin, Mohd Shaberi (2002)
A senes of chelating resins, derived from a macroreticular styrenedivinylbenzene (2%) copolymer beads grafted with various spacer from propylene groups (-CH₂-CH₂-CH₂)n (n=1, 2, 4) and containing thiourea as chelating function, have been synthesized in a four-step reaction sequence. The steps began by the reaction of diethyl malonate with a spacer (ethylene groups), followed with the attachment of the arm group to the polymer. The polymer was then hydrolyzed and converted to its polychloride acid derivatives and followed by the attachment of the thiourea functional group to produce the new chelating resins. The reaction of diethyl malonate with the spacer has been monitored by using nuclear magnetic. resonance analysis. Meanwhile, the presence of all the functional groups has been deduced by infrared spectroscopy. Due to the insolubility of the backbone resin, the presence or absence of certain bands expected for particular functional groups in their infrared spectra was used to monitor the success of the grafting process. The C, H, N and S elemental analyses data were used to estimate the degree of conversion in each and every step of the reactions and the surface morphology was studied by using scanning electron microscopy. The complexation behavior of these resins was investigated towards Hg(II), Cu(II) and Pb(II) ions in aqueous solutions by the batch equilibration technique. The influence of pH on adsorption capacity was also examined. The adsorption values for metal ions' intake followed the order Hg(II) > Cu(II) > Pb(II). Polymers can be regenerated by washing with the mixture solution of hydrochloric acid and an aqueous solution of thiourea by using the column method.